Prinsip Empan Papan sebagai Strategi Komunikasi Efektif dalam Menciptakan Kenyamanan Mahasiswa Perantau Etnis Jawa - Septiana, Asti Arinta; Salsabila, Saniya Alin (Lembaga Kajian, Penelitian dan Pengembangan Mahasiswa Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This study aims to analyze the Empan Papan principle as an effective communication strategy for overseas students at UIN Maulana Malik Ibrahim Malang. In a multicultural campus environment, overseas students face cross-cultural communication challenges that can hinder social and academic adaptation. The Empan Papan principle from Javanese culture emphasizes adjusting speech and actions according to the situation, place, and social conditions. This study uses a descriptive qualitative approach through in-depth interviews with five Javanese ethnic overseas students from various regions. The results show that the Empan Papan principle strengthens interpersonal relationships and reduces communication misunderstandings. This strategy also builds social sensitivity and mutual respect among cross-cultural students. The Empan Papan principle proved to be relevant as a cultural approach in supporting effective communication and successful adaptation of overseas students in the academic environment.